Antihyperalgesic Properties of Honokiol in Inflammatory Pain Models by Targeting of NF-κB and Nrf2 Signaling - Khalid, Sidra (Front Pharmacol, 2018)
The present study investigates the possible anti-nociceptive effect of intraperitoneal (i.p.) honokiol: a phenolic compound originally isolated from Magnolia officinalis, in acute and chronic inflammatory pain models. Doses of 0.1, 5, and 10 mg/kg honokiol were administered in carrageenan induced pain and the dose (honokiol 10 mg/kg i.p.) with most significant response among behavioral tests was selected for further experiments. The i.p. administration of honokiol inhibits mechanical hyperalgesia, mechanical allodynia, and thermal hyperalgesia, without causing any apparent toxicity. To elucidate the effect of honokiol on various cytokines and antioxidant enzymes, quantitative real-time-PCR was performed to determine the expression levels of pro-inflammatory cytokines and antioxidant enzymes. It is demonstrated that honokiol significantly reduced the expression levels of tumor necrosis factor (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6), and vascular endothelial growth factor (VEGF). Similarly, honokiol was also found to potentiate the expression of nuclear factor erythroid 2–related factor 2 (Nrf2), superoxide dismutase 2 (SOD2), and heme oxygenase-1 (HO-1) levels. Additionally, honokiol significantly reduced plasma nitrite levels as compared to complete Freund’s adjuvant (CFA) induced group. X-ray analysis and hematoxylin and eosin (H&E) staining of inflamed and treated paws showed that honokiol reduced the inflammation with significantly less leukocyte infiltration and soft tissue inflammation. In order to explore the possible mechanism of action of honokiol, agonists [piroxicam (5 mg/kg), tramadol (50 mg/kg), and gabapentin (5 mg/kg) i.p.] as well as antagonists [naloxone (4 mg/kg), olanzapine (10 mg/kg), and flumazenil (0.2 mg/kg) i.p.] were used to study involvement of various receptors on the anti-nociceptive effect of honokiol. The potential side effects of honokiol on muscle activity were assessed. An adverse effect testing of honokiol by liver and renal functions were also carried out. The effect of oral honokiol was also assessed on gastrointestinal (GIT) mucosa. Our results demonstrate that honokiol has a significant anti-nociceptive activity through inhibition of anti-inflammatory mediators.